Author’s Epithet in A. Casona’s Dramas: Features of Functioning and Problem of Translation - V. V. Shchepalina (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The article is devoted to art techniques most typical to A. Casona’s idiostyle - the author’s epithet - in the aspect of translation into Russian. The term “ author’s epithet ” means an unexpected, non-reproducible combination enriching the writer’s native language. The relevance of the study is due to the fact that it is difficult to find an equivalent for the author’s epithet in translation due to language asymmetry, mismatch of lexical compatibility of direct equivalents. The article provides an overview of studies on the translation of drama, as well as the extralinguistic factors that impose restrictions on the translator. The author analyzes her own translations of two plays belonging to different periods of the playwright’s work. Methods of contextual, component, discursive and stylistic analysis, method of observation, generalization and description are used in the work. The study suggests that the high frequency of use, structural diversity, the ability to express the functions of various means of artistic expression (metaphor, metonymy, impersonation, antithesis, etc.) make epithet one of the most productive artistic techniques in Casona’s drama. The functional approach to its translation is substantiated. The scientific novelty of the article is associated with a small study of Casona’s creativity both by domestic and foreign researchers.